E-waste management in Sub-Saharan Africa: A systematic literature review - Vusumuzi Maphosa; Mfowabo Maphosa (Cogent Business & Management, 2020)
The developing world has become the primary destination for used electrical and electronic equipment (EEE) exported by the developed world, making e-waste management critical. This paper aims to determine the state of e-waste management in Sub-Saharan Africa by critically reviewing the corpus on electronic waste (e-waste) management in the region. Even though many studies were conducted on e-waste management, very few are conducted on developing countries who are significant recipients of used EEE. We applied a systematic literature review (SLR) process on research articles retrieved from Web of Science, EBSCO Host and Sabinet databases. Using the keywords that included e-waste management or recycling or policy in Sub-Saharan Africa or Africa, we searched for articles from these databases. We analysed 25 papers selected from 151,558 papers initially retrieved to answer the research questions. The findings revealed that about 80% of research on e-waste management in the Sub-Saharan Africa region was undertaken in three countries: Ghana, Nigeria, and South Africa. The review of the selected articles revealed that lack of policy and limited recycling infrastructure were the main barriers to effective e-waste management. The SLR revealed that most countries in the region practice informal and rudimentary recycling methods. Based on the common barriers identified, our recommendations can provide insight to policymakers, contribute to theory, and offer opportunities for future research.
Keywords: 650; e-waste; e-waste management; recycling; environment; policy; landfills; health